PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI KANTOR DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN KONAWE - Bindarto Bindarto (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
Effect of Leadership Style, Organizational Culture and Organizational Commitment on Employee Performance of the Office of Population and Civil Registry of Konawe Regency, this study aims to analyze how much influence the Leadership Style, Organizational Culture and Organizational Commitment on employee performance at the Office of Population and Civil Registry Office of Konawe Regency. The population in this study amounted to 35 employees of the Office of Population and Civil Registry of Konawe Regency, with sampling techniques using saturated sample techniques. The analytical method used is multiple linear regression analysis. The results of this study indicate that simultaneously the variables of Leadership Style, Organizational Culture and Organizational Commitment have a significant and positive effect on employee performance.